1959
DOI: 10.1063/1.1730144
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation, Rotation, and Spin Relaxation in NO

Abstract: The sound absorption and velocity of NO gas at 293°K was measured from f/p=5×104 to 107 cps/atmos using an ultrasonic pulse method. A maximum of the absorption at 4×105 cps/atmos is ascribed to the relaxation of the oscillational degree of freedom. (τosc=4×10—7 sec at 1 atmos.) According to the absorption at high f/p values, τspin≈4τrot (=2.5·10—9 sec at 1 atmos) seems probable. The result is compared to the corresponding data of O2 and N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1961
1961
1997
1997

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Thus it is found that the value of P,_0 for NO is 3.6 ? 0.4 X 10---at 300?K, in good agreement with the sound-propagation results of Bauer et al(17) and the extrapolated shock-wave results of Robof P,0_ for nitrogen is very small; it is calculated as 4 X 10-7 within an order of magnitude. Data for other gases, such as CO, CO and Kr, as quenching agents have been obtained by using them as coolant additives in a similar way; CO and CO2 give P,_o values of 0.25 X 10-4 and 1.7 X 10-4 respectively but krypton is totally without effect in quenching.By flashing with the photoflash alone it is possible to photograph the fluorescent emission progressions from v' latter case; but if the fluorescence levels is completely quenched by sufficient additive the (v -1) level is still observed to be over-populated in the ground state.…”
supporting
confidence: 89%
“…Thus it is found that the value of P,_0 for NO is 3.6 ? 0.4 X 10---at 300?K, in good agreement with the sound-propagation results of Bauer et al(17) and the extrapolated shock-wave results of Robof P,0_ for nitrogen is very small; it is calculated as 4 X 10-7 within an order of magnitude. Data for other gases, such as CO, CO and Kr, as quenching agents have been obtained by using them as coolant additives in a similar way; CO and CO2 give P,_o values of 0.25 X 10-4 and 1.7 X 10-4 respectively but krypton is totally without effect in quenching.By flashing with the photoflash alone it is possible to photograph the fluorescent emission progressions from v' latter case; but if the fluorescence levels is completely quenched by sufficient additive the (v -1) level is still observed to be over-populated in the ground state.…”
supporting
confidence: 89%
“…The errors from photometry of the absorption spectra show that these data are accurate to about ± 10 % (the origin of these and other inaccuracies is now understood and more accurate results should be obtainable). The reciprocal relaxation time can be split into two terms k3 = *4(NO) + *5(N 2) thus yielding a value for P10 for NO of 3-6 + 0-4 x 10~4 (in excellent agreement with sound absorption (Bauer et al 1959) and the extrapolated shock wave results (Robben 1959)) and P1_0 for N2 of 4 x 1 0 7, the latter quantity being accurate to within an order of magnitude.…”
Section: Quantum Yield and Temperature Risementioning
confidence: 54%
“…The relaxation time in Kr + NO mixtures depended only on the partial pressure of NO and the temperature. Relaxation of vibration and spin orbit coupling has recently been described by Bauer, Kneser & Sittig (1959) measured by sound absorption; they recorded P01 = 3-8 x 10-4 at 20 °C and spin orbit relaxation occurred once in sixteen collisions.…”
mentioning
confidence: 94%
“…This is similar to Fig. I except that 0, has replaced H 2 0 , and all the arrows [17] to [27] indicating previous reaction paths have been omitted in Fig. 2 for clarity.…”
mentioning
confidence: 60%
“…For NO the V + T process has been studied over a wide temperature range for M = Ar and NO (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). For M = H,O, CO,, N,, and CO there are only measurements at 300 "K (28).…”
Section: Comentioning
confidence: 99%